Studies on Engineering Properties of Pelleted Carrot (Daucus carota L.) Seeds - Gautam, Anand; Khurana, Rohinish; Manes, G. S.; Dixit, Anoop Kumar (International Journal of Bio-resource and Stress Management, 2016)
Carrot (Daucus carota L.) commonly known as Gajar. Certain limitations associated with the production, processing and effective utilization of small seeds. Carrot seeds are small in size and difficult to handle for sowing purpose. For the development of a mechanism for carrot seed sowing the study of engineering properties of carrot seeds is of utmost importance. The biometric properties of seeds play an important role in designing seed metering device. Physical and engineering properties of carrot seed both un-pelleted and pelleted were evaluated in the laboratory. Therefore, the physical properties of the carrot seeds such as size, shape, thousand grain weight, and angle of repose, bulk density and coefficient of static friction are important from engineering view point and were studied for cultivars of carrot i.e. deshi red pelleted were compared with un-pelleted carrot seeds. The geometric mean diameter (GMD) was 2.03, 2.19, 2.39 and 2.70 mm for deshi red carrot seeds, respectively. The average values of angle of repose for the cultivars under study as observed in the laboratory was 32.79°, 30.37°, 28.87° and 28.00° respectively for deshi red carrot seeds. The values of porosity are decreased gradually in seeds whereas the porosity for seed having GMD 2.70 mm was 50.84% and is the lowest amongst the other cultivars. The porosity of un-pelleted seed was the highest (64.96%).